Membrane Technologies for Separating Volatile Fatty Acids Produced Through Arrested Anaerobic Digestion: A Review - Angana Chaudhuri; Budi Mandra Harahap; Birgitte K. Ahring (Clean Technologies, 2025)
Volatile fatty acids (VFAs) are important precursors used in various industrial applications. Generally, these carboxylic acids are produced from oil, but recently focus has been on the development of biological methods for substituting the fossil raw material with organic waste and lignocellulosic materials. This is possible by stopping the anaerobic digestion process at the level of VFA through elimination of the final step of methanogenesis. The primary barrier to commercial viability of VFA production is the costly downstream processing needed for separation of the VFA’s. Existing separation techniques, such as adsorption and liquid–liquid extraction, achieve nearly complete VFA recovery from fermentation broths but require substantial chemical inputs and extensive preprocessing. In contrast, membrane-based separation processes could potentially overcome the need for chemical additions and provide a more sustainable way of separation. In this review we examine the current state of the art of membrane technology for VFA separation. We assessed and compared the capital and operational costs associated with different membrane technologies and identified the major hurdles impeding their commercialization. Furthermore, we examine hybrid and emerging membrane technologies that previous studies have suggested to reduce both energy and capital costs. Finally, we present future perspectives for the development of cost-effective membrane technologies suitable for industrial-scale applications.